Transgenerational epigenetic variance for body weight in meat quails. (June 2018) - Paiva, J.T.; de Resende, M.D.V.; Resende, R.T.; de Oliveira, H.R.; Silva, H.T.; Caetano, G.C.; Lopes, P.S.; Silva, F.F.
Summary: We aimed to estimate transgenerational epigenetic variance for body weight using genealogical and phenotypic information in meat quails. Animals were individually weighted from 1 week after hatching, with weight records at 7, 14, 21, 28, 35 and 42 days of age (BW7, BW14, BW21, BW28, BW35 and BW42, respectively). Single‐trait genetic analyses were performed using mixed models with random epigenetic effects. Variance components were estimated by the restricted maximum likelihood method. A grid search for values of autorecursive parameter (λ) ranging from 0 to 0.5 was used in the variance component estimation. This parameter is directly related to the reset coefficient (ν) and the epigenetic coefficient of transmissibility (1‐ν). The epigenetic effect was only significant for BW7. Direct heritability estimates for body weight ranged in magnitude (from 0.15 to 0.26), with the highest estimate for BW7. Epigenetic heritability was 0.10 for BW7, and close to zero for the other body weights. The inclusion of the epigenetic effect in the model helped to explain the residual and non‐Mendelian variability of initial body weight in meat quails.